Quantitative analysis of fetal DNA in maternal plasma in gestational diabetes mellitus, iron deficiency anemia and gestational hypertension pregnancies - Zamanpoor, Mansour; Rosli, Rozita; Yazid, Mohd Nazri; Husain, Zaheed; Nordin, Norshariza; Karuppiah, Thilakavathy (Taylor & Francis, 2013)
Objective: To quantify circulating fetal DNA (fDNA) levels in the second and third trimesters of normal healthy pregnant individuals and pregnant women with the following clinical conditions: gestational diabetes mellitus (GDM), iron deficiency anemia and gestational hypertension (GHT). Methods: The SRY gene located on the Y chromosome was used as a unique fetal marker. The fDNA was extracted from maternal plasma and the SRY gene concentrations were measured by quantitative real-time polymerase chain reaction (PCR) amplification using TaqMan dual labeled probe system.